2017
DOI: 10.1074/jbc.m116.756627
|View full text |Cite
|
Sign up to set email alerts
|

TNF-stimulated gene 6 promotes formation of hyaluronan–inter-α-inhibitor heavy chain complexes necessary for ozone-induced airway hyperresponsiveness

Abstract: Exposure to pollutants, such as ozone, exacerbates airway inflammation and hyperresponsiveness (AHR). TNF-stimulated gene 6 (TSG-6) is required to transfer inter-α-inhibitor heavy chains (HC) to hyaluronan (HA), facilitating HA receptor binding. TSG-6 is necessary for AHR in allergic asthma, because it facilitates the development of a pathological HA-HC matrix. However, the role of TSG-6 in acute airway inflammation is not well understood. Here, we hypothesized that TSG-6 is essential for the development of HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…37 Moreover, inhibition of PI3K/Akt signalling pathways have been shown to block tumour necrosis factor-stimulated gene 6-mediated acute airway inflammation and hyper-responsiveness in response to ozone or short-fragment HA. 38 Here we confirm that the inclusion of PI3K as an upstream activator of Akt1 was confirmed by using specific inhibitors, wortmannin and LY2940002, which consistently suppressed Akt1 phosphorylation and neutrophil counts. Akt1 is regulated by PI3K in LMMHA-induced neutrophil responses.…”
Section: Discussionsupporting
confidence: 81%
“…37 Moreover, inhibition of PI3K/Akt signalling pathways have been shown to block tumour necrosis factor-stimulated gene 6-mediated acute airway inflammation and hyper-responsiveness in response to ozone or short-fragment HA. 38 Here we confirm that the inclusion of PI3K as an upstream activator of Akt1 was confirmed by using specific inhibitors, wortmannin and LY2940002, which consistently suppressed Akt1 phosphorylation and neutrophil counts. Akt1 is regulated by PI3K in LMMHA-induced neutrophil responses.…”
Section: Discussionsupporting
confidence: 81%
“…Our recent study identi ed that TSG-6 is expressed in the central nervous system (CNS), where it catalyzes the transfer of heavy chains (HCs) from Inter-a-Inhibitor (IaI, also known as ITI) onto HA, forming a specialized HA/HC/TSG-6 matrix within the glial scar, but the role of this specialized matrix within the glial scar remains to be established (42,(48)(49)(50)(51)(52). The HA/HC/TSG-6 matrix has been shown to be monocyte-adhesive and is found in most, if not all, in ammatory processes (53,54). These TSG-6 modi ed HA matrices bind in ammatory cells, and the interaction of these cells with the HA matrices modulates their responses, which are central to pathological in ammation (55)(56)(57)(58)(59)(60)(61).…”
Section: Introductionmentioning
confidence: 99%
“…We recently identified that TSG-6 is expressed in the central nervous system (CNS), where it catalyzes the transfer of HCs from Inter-a-Inhibitor (IαI, also known as ITI) onto HA, forming a specialized HA/HC/TSG-6 matrix within the glial scar (47)(48)(49)(50)(51)(52). This HA/HC/TSG-6 matrix is monocyte-adhesive and is found in most, if not all, inflammatory processes (53,54). These TSG-6 modified HA matrices bind inflammatory cells, and the interaction of these cells with the HA matrices modulates their responses, which are central to pathological inflammation (55)(56)(57)(58)(59)(60)(61).…”
Section: Introductionmentioning
confidence: 99%